2015
DOI: 10.1073/pnas.1500605112
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome dynamics of developing maize leaves and genomewide prediction ofciselements and their cognate transcription factors

Abstract: Maize is a major crop and a model plant for studying C4 photosynthesis and leaf development. However, a genomewide regulatory network of leaf development is not yet available. This knowledge is useful for developing C3 crops to perform C4 photosynthesis for enhanced yields. Here, using 22 transcriptomes of developing maize leaves from dry seeds to 192 h post imbibition, we studied gene up-and down-regulation and functional transition during leaf development and inferred sets of strongly coexpressed genes. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 85 publications
0
60
1
4
Order By: Relevance
“…A widely used approach to elucidate the function of a TF is to perturb the given TF and compare expression profiles of the wild-type and perturbed states, leading to lists of differentially expressed genes on which de novo motif finding often is performed to obtain new insights on the regulation of these genes. The combination of these motifs with conservation analysis is a powerful approach to identify genome-wide bona fide target genes with these motifs and can help to unravel the underlying regulatory cascade, as was shown recently for leaf development in maize (Zea mays; Yu et al, 2015). Another approach in which CNSs can play a key role is the translation of existing knowledge of GRNs in model species into economically more interesting species, which is not trivial, owing to the occurrence of evolutionary changes.…”
Section: Discussionmentioning
confidence: 99%
“…A widely used approach to elucidate the function of a TF is to perturb the given TF and compare expression profiles of the wild-type and perturbed states, leading to lists of differentially expressed genes on which de novo motif finding often is performed to obtain new insights on the regulation of these genes. The combination of these motifs with conservation analysis is a powerful approach to identify genome-wide bona fide target genes with these motifs and can help to unravel the underlying regulatory cascade, as was shown recently for leaf development in maize (Zea mays; Yu et al, 2015). Another approach in which CNSs can play a key role is the translation of existing knowledge of GRNs in model species into economically more interesting species, which is not trivial, owing to the occurrence of evolutionary changes.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomes of different regions of a growing leaf, representing different developmental stages, were compared by Li et al (2010) and Pick et al (2011). Transcriptional dynamics during early development of embryonic leaves were surveyed by Liu et al (2013b) and Yu et al (2015). Additionally, the regulatory and functional differentiation of various leaf cell types was examined by transcriptome analysis (Li et al, 2010;Wang et al, 2013Wang et al, , 2014.…”
mentioning
confidence: 99%
“…Although analyses of transcriptional variation during maize leaf development have provided us with new insights, all these studies were restricted to one genetic background (Li et al, 2010;Pick et al, 2011;Liu et al, 2013b;Wang et al, 2013Wang et al, , 2014Yu et al, 2015). Adding an additional layer of information, phenotypic variation in mapping populations, and combining this with transcriptome variation in these populations offers new opportunities to identify genes and regulatory mechanisms that are at the basis of phenotypic differences (Andorf et al, 2012).…”
mentioning
confidence: 99%
“…5A and B) revealed that unigenes belonging to 13 MapMan bins might have been enriched during the C4-associated evolution (Supplementary Table S12). Among the enriched unigenes, those assigned to the "Cell wall", "RNA", and "Development" classes, which have been pointed out to contribute to the differentiation and development of C4 -specific mesophyll and bundle-sheath cells (Chang et al, 2013;Yu et al, 2015), were found. For example, 4 of the SCARECROW genes and 2 of SHORT ROOT genes both of which are suggested to be involved in the development of bundle sheath cells Gao et al, 2014) and 2 of the nodulin (Nodule inception 1 genes which are reported to be involved in vascular strand formation in gramineous plants (Gamas et al, 1996) and Kranz structure development (Chang et al, 2012) were found in the "Development" class.…”
Section: Expanded Gene Families In C4 Plantsmentioning
confidence: 99%